2017
DOI: 10.3201/eid2303.161006
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Tuberculosis Cases among Prisoners, Brazil, 2009–20141

Abstract: During 2009–2014, incarceration rates in Brazil rose 34%, and tuberculosis (TB) cases among prisoners rose 28.8%. The proportion of national TB cases that occurred among prisoners increased from 6.2% to 8.4% overall and from 19.3% to 25.6% among men 20–29 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
3
21
0
1
Order By: Relevance
“…These data suggest that a significant portion of the prison population may leave the state following release, and so TB incidence among ex-prisoners may be considerably higher than we have calculated. We assumed that the TB epidemic in the community and prisons is at steady state, and population-level incidence has changed by <5% in the past 15 years; if TB incidence disparities are growing, as some evidence suggests [17], our model would underestimate the benefits of interventions targeted in the prisons. Our model is a simplification of a complex process; we deliberately chose a parsimonious model structure that builds directly upon widely used models in the TB literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that a significant portion of the prison population may leave the state following release, and so TB incidence among ex-prisoners may be considerably higher than we have calculated. We assumed that the TB epidemic in the community and prisons is at steady state, and population-level incidence has changed by <5% in the past 15 years; if TB incidence disparities are growing, as some evidence suggests [17], our model would underestimate the benefits of interventions targeted in the prisons. Our model is a simplification of a complex process; we deliberately chose a parsimonious model structure that builds directly upon widely used models in the TB literature.…”
Section: Discussionmentioning
confidence: 99%
“…With a population of 2.6 million, the state of Mato Grosso do Sul lies in central-west Brazil, adjoining Paraguay and Bolivia. The state has the highest incarceration rate in Brazil (475 prisoners per 100,000 individuals), driven primarily by drug trafficking across country borders [17].…”
Section: Methodsmentioning
confidence: 99%
“…Despite being a minority, the research showed a higher proportion of treatment failure in women (71.4%) than in men (26.3%). A study assessing TB in the Brazilian PPL from 2009 to 2014 11 showed that women deprived of liberty had HIV co-infection rates (24.1%) higher than men (15.2%). In this study, co-infection appeared in 28.6% of women and 5.5% of men, and may contribute significantly to the observed failure scenario, though associated with other characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a survey carried out for the national notification database, in 2009-2014, TB cases among prisoners increased by 28.8%. 21 Corroborating these data, in the 12 prisons in the central-west region, a prevalence of 0.7% was found at baseline and 1.8% 1 year later. 14 At the regional level, there is little data on São Paulo state.…”
Section: Discussionmentioning
confidence: 82%